Nonlinear Differential Equations with Distributed Delay: Some New Oscillatory Solutions - Almarri, Barakah; Ali, Ali Hasan; Lopes, António M.; Bazighifan, Omar (Mathematics (Basel), 2022)
The oscillation of a class of fourth-order nonlinear damped delay differential equations with distributed deviating arguments is the subject of this research. We propose a new explanation of the fourth-order equation oscillation in terms of the oscillation of a similar well-studied second-order linear differential equation without damping. The extended Riccati transformation, integral averaging approach, and comparison principles are used to provide some additional oscillatory criteria. An example demonstrates the efficacy of the acquired criteria.